César Franck: His Life and Times - Stove, R. J. (Rowman & Littlefield Publishers, 2011)
César Franck (1822–1890), Belgian born and French domiciled, was one of the most remarkable composers of the 19th century. A number of his works are commonly recorded—such as his Symphony in D Minor, Symphonic Variations, Violin Sonata, and the ever-popular Panis Angelicus—and yet 38 years have elapsed since a biography of him appeared in English. Now with César Franck: His Life and Times, R. J. Stove fills this gap in the history of late 19th-century classical music with a full-length study of the man and his music. Drawing on sources never before cited in English, Stove paints a far more detailed picture of this great musician and deeply loved man, whose influence in both his native and adopted lands was exceptional. Stove carefully delves into intimate matters of Franck’s life, including his resilience in the face of his exploitation as a child prodigy at the piano, his development from a shy and harassed piano teacher into one of the most sought-after luminaries of Paris’s Conservatoire, and the truth behind Franck’s alleged affair with one of his students. Throughout his study, Stove interweaves panoramic surveys of the political and social scene in Belgium and France, contextualizing Franck’s achievements in his historical milieu, from his rise as a recognized master of the organ to his dealings with significant composers such as Liszt, Gounod, Saint-Saëns, Massenet, Chabrier, and others. César Franck: His Life and Times is an engagingly written biography sure to interest classical music listeners of all stripes.